A select library of the Nicene and Post-Nicene Fathers of the Christian church - Augustin, Saint; Augustine, Saint; Schaff, Philip, 1819-1893 (Edinburgh, Scotland T and T Clark, 1889)
Contents: vol II : Saint Augustin / City of God; Christian doctrine. Includes indexes.
Keywords: Fathers of the church -- primitive and early church -- ca. 30-600.; Augustin, Saint; Augustine, Saint